Effects of filtration methods and water volume on the quantification of brown trout (Salmo trutta) and Arctic char (Salvelinus alpinus) eDNA concentrations via droplet digital PCR. Issue 2 (17th November 2019) - Capo, Eric; Spong, Göran; Königsson, Helena; Byström, Pär
Abstract: The quantification of the abundance of aquatic organisms via the use of environmental DNA (eDNA) molecules present in water is potentially a useful tool for efficient and noninvasive population monitoring. However, questions remain about the reliability of molecular methods. Among the factors that can hamper the reliability of the eDNA quantification, we investigated the influence of five filtration methods (filter pore size, filter type) and filtered water volume (1 and 2 L) on the total eDNA and the fish eDNA concentrations of two species, brown trout ( Salmo trutta ) and Arctic char ( Salvelinus alpinus ) from tanks with known number of individuals and biomass. We applied a droplet digital PCR (ddPCR) approach to DNA extracted from water samples collected from two cultivation tanks (each of them containing one of the targeted species). Results showed that the quantification of fish eDNA concentrations of both species varies with filtration methods. More specifically, the 0.45‐µm Sterivex enclosed filters were identified to recover the highest eDNA concentrations. Difficulties to filter 2 L water samples were present for small pore size filters (≤0.45 µm) and likely caused by filter clogging. To overcome issues related to filter clogging, common in studies aiming to quantify fish eDNA molecules from water samples, we recommend a procedure involving filtration of multiple 1 L water samples with 0.45‐µm enclosed filters, to recover both high quality and high concentrations of eDNA from targeted species, and subsequent processing of independent DNA extracts with the ddPCR method. Abstract : We investigated the influence of the five filtration methods and filtered water volume (1 and 2 L) on the total eDNA and the fish eDNA concentrations of two species, brown trout ( Salmo trutta ) and Arctic char ( Salvelinus alpinus ) from tanks with known number of individuals and biomass. Our results allow us to recommend the filtration of multiple 1 L water samples with 0.45‐µm enclosed filters that showed the best efficiency to recover good quality DNA alongside with the highest rate of eDNA concentrations from targeted species.